1996
DOI: 10.1016/0167-5877(95)00561-7
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effects of specific egg-yolk antibodies on diarrhea of newborn calves

Abstract: In a field trial on a farm in Turkey, we tested whether specific egg-yolk antibodies had a prophylactic effect on neonatal diarrhea. Owing to its antibody spectrum, this egg powder was very suitable for this farm since mainly rotavirus was identified. Regardless of the dosage (2 g, 4 g, or 8 g egg powder), the calves (n = 164) which received specific egg-yolk antibodies via the whole egg during the first 14 days of life showed significant improvements in risk and duration of diarrhea and in body weight gain co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…Studies using both animal models and trials in field herds have been carried out. The groups of Erhard ( 179), Lösch (180)(181)(182), Yolken (183) and Kuroki (171,172) have performed a great part of the studies on the practical use of IgY. These studies confirmed that the treatment of diarrhoea in calves and piglets with specific egg yolk Abs has achieved significant prophylactic and therapeutic benefits.…”
Section: Igy For Therapeutical or Prophylactic Use In Veterinary Medimentioning
confidence: 93%
“…Studies using both animal models and trials in field herds have been carried out. The groups of Erhard ( 179), Lösch (180)(181)(182), Yolken (183) and Kuroki (171,172) have performed a great part of the studies on the practical use of IgY. These studies confirmed that the treatment of diarrhoea in calves and piglets with specific egg yolk Abs has achieved significant prophylactic and therapeutic benefits.…”
Section: Igy For Therapeutical or Prophylactic Use In Veterinary Medimentioning
confidence: 93%
“…A large number of authors have stated that egg yolk antibodies administered to different types of animals can be used for the prevention and therapy of infectious diseases, especially diseases affecting the gastrointestinal tract. Yolk antibodies have been used successfully in cases of diarrhoea of unweaned piglets and newborn calves (Erhard et al., 1993; Kellner et al., 1994; Özpinar et al., 1996). In most of the scientific reports on mammals, clinical findings were linked directly to the protective effects of administered egg yolk antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Authors working with egg yolk antibodies to control new born diarrhoea in calves (Erhard et al., 1993; Özpinar et al., 1996) or unweaned piglets (Wiedemann et al., 1990; Kellner et al., 1994) stated that orally administered specific yolk antibodies reach the intestine unchanged similar to the colostral antibodies in the first days of life (Wiedemann et al., 1990).…”
Section: Discussionmentioning
confidence: 99%
“…IgY has been shown to successfully control intestinal infection of rotavirus in newborn calves and mice [ 70 73 ]. Studies with pigs have been reported and similar positive results were obtained [ 74 ].…”
Section: Antiviral and Performance Effectsmentioning
confidence: 99%